Postural Stability Characteristics of Transtibial Amputees Wearing Different Prosthetic Foot Types When Standing on Various Support Surfaces - Nooranida Arifin; Noor Azuan Abu Osman; Sadeeq Ali; Hossein Gholizadeh; Wan Abu Bakar Wan Abas (The Scientific World Journal)
Purpose. This study aimed to evaluate the effects of prosthetic foot types on the postural stability among transtibial amputees when standing on different support surfaces. Materials and Methods. The postural stability of 10 transtibial amputees wearing solid ankle cushion heel (SACH) foot, single-axis (SA) foot, and energy-saving and return (ESAR) foot was assessed. Results were compared with able-bodied participants. Anterior-posterior stability index (APSI), mediolateral stability index (MLSI), and overall stability index (OSI) were measured by computed posturography in an upright stance on firm, foam, and unstable support surfaces. Results. The mean OSI score of SACH foot was significantly lower than that of an ESAR foot when the participants were standing on a compliant surface. When compared to able-bodied group, MLSI score was significantly higher for each of the prosthetic foot groups while OSI score was significantly higher for ESAR foot only in foam condition. Conclusions. Differences between prosthetic foot types and groups (amputees versus able-bodied) can only be distinguished when individuals were standing on a compliant surface. Amputees exhibited an increased postural instability in the mediolateral direction than able-bodied individuals. Hence, the restoration of stability in the frontal plane and the enhancement of proprioception at the residual limb should be the basis of rehabilitation programs.